A long road to recovery: dynamics and ecology of the marbled rockcod (Notothenia rossii, family: Nototheniidae) at South Georgia, 50 years after overexploitation. (18th August 2021) - Hollyman, Philip R; Hill, Simeon L; Laptikhovsky, Vladimir V; Belchier, Mark; Gregory, Susan; Clement, Alice; Collins, Martin A
Abstract: Exploitation is one of the major drivers of change in marine ecosystems. Following discovery in 1775, South Georgia saw sequential overexploitation of living resources, including seals, whales, and fish. Although exploitation is now tightly regulated, the ecosystem is still recovering. Marbled rockcod, Notothenia rossii (Richardson 1844), was the first fish species to be commercially exploited and high catches between 1967 and 1972 resulted in dramatic stock decline. Here, we use 30 years of trawl survey data to provide the first evidence of a sustained increase in the N. rossii population starting two decades after the prohibition of targeted fishing in 1985. The way species respond to change is mediated in part by trophic relationships with other organisms. We present the first multi-year, spatially-resolved comparison of adult N. rossii diet at South Georgia, highlighting a variable diet with less reliance on Antarctic krill than previously thought. Life history factors and possible heavy predation on early life stages might have delayed their recovery while diet plasticity potentially supported recent population growth. Due to the dynamic ecosystem at South Georgia and questions over catch reports from the period of heaviest exploitation, it is unlikely the current ecosystem could support a recovery to estimated pre-exploitation levels.